Further exploring the feasibility of dendritic cells-targeted biomimetic Texosomes as a therapeutic and preventive tumor-vaccine. Issue 16 (31st January 2017) - Li, Kexin; Chang, Shasha; Zhao, Xiuli; Chen, Dawei
Abstract : Targeting tumor cells with immunotherapy by a dendritic cells-targeted vaccination is a potential treatment option. Abstract : Targeting tumor cells with immunotherapy by a dendritic cells-targeted vaccination is a potential treatment option. In previous research, we preliminarily proved the immune activity of hTERT-HSP70 loaded DEC205McAb Texosomes on H22 hepato-carcinoma bearing mice. In this article, in order to further verify the feasibility of DEC205McAb Texosomes as a new type of anti-tumor vaccine in clinical treatment, we also inspected the vaccine's broad spectrum, the best immune period, the vaccine's preventability, and moreover the influence of immune inhibitors on this vaccine. Anti-tumor immune responses were evaluated by determining the tumor volume, mice survival rate, and the IL-12 and IFNγ antibody levels. Our results suggest that DEC205McAb Texosomes could also efficiently inhibit the tumor growth of S180 ascites sarcoma bearing mice with a 7 day immune period, and we also found that DEC205McAb Texosomes as an anti-tumor vaccine could achieve not only good therapeutic treatment but also effective preventive performance. In conclusion, we hope that dendritic cells-targeted anti-tumor vaccines could become a new approach in the field of cancer treatment and prevention.